Development of Children’s Songs Using Musescore Applications in Learning Aspect of Development for Early Childhood - Rantina, Mahyumi; Hasmalena, Hasmalena; Yosef, Yosef (International Conference on Elementary Education, 2020)
This study aims to develop products in the form of Development of Children's Songs Using Musescore Applications in Learning Aspects of Early Childhood Development. This research is a Research and Development (R&D) model of ADDIE. The product trials were conducted by two expert namely material experts and media design experts with a valid category with a percentage of eligibility 75.5 and 78% respectively so that the product was eligible to be continued in small-scale trials. A small group trial was conducted on respondents totaling ten teachers and ten students. Furthermore, to find out the effectiveness of the use of songs in PAUD, an evaluation is carried out by means of pretest and posttest. The average pretest value obtained was 63%, while the average posttest value was 82% with effectiveness based on the n-gain formula of 0.68 in the medium category. In a large group trial, the average score of the pretest respondents was 42%, and the average post-test score was 81% with an effectiveness level of 0.67 in the medium category. So, it can be concluded that the Development of Children's Songs Using Musescore Applications in Learning Aspects of Early Childhood Development as valid, practical and effective is used by Early Childhood